Anti-nociceptive effect of black seed oil on an animal model of chronic constriction injury - Sayyed Alireza Talaei; Hamid Reza Banafshe; Alireza Moravveji; Mohammad Shabani; Shiva Shirazi Tehrani; Alireza Abed (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: Traditionally, Nigella sativa L. has been known as a medical intervention to treat numerous diseases. This study aimed at investigating the antihyperalgesic effect of black seed oil (BSO) in an experimental model of neuropathic pain. Experimental approach: Chronic constriction injury (CCI) was performed under anesthesia. The sciatic nerve was ligated with four loose ties. Two separate protocols were used to administer BSO. In chronic treatment, rats were given daily doses of BSO (250, 500, and 1000 mg/kg p.o.) from the 1st day until the 21st post-CCI day. While, in acute treatment, BSO (250, 500, and 1000 mg/kg p.o.) was administered only on the 7th, 14th, and 21st days. CCI and sham groups were given almond oil according to the same schedule. Behavioral scores were determined by evaluation of the paw withdrawal in the plantar, Von Frey, and acetone tests, on the 7th, 14th, and 21st days. Findings/Results: Our results showed that CCI leads to significant allodynia and hyperalgesia in the ipsilateral paw after surgery. Chronic administration of BSO (500 and 1000 mg/kg) obviously attenuated heat hyperalgesia and mechanical allodynia. However, daily administration of BSO did not alter cold allodynia. Nevertheless, when BSO was administered, 30 min before the pain assessment tests, hypersensitivity was not improved in the treated animals. Conclusion and implications: These results demonstrated BSO can inhibit neuropathic pain progression and suggests a potential use of BSO to manage hyperalgesia and allodynia. However, additional research is necessary to approve BSO effectiveness, in neuropathic pain conditions.